STUDENT RADIOGRAPHERS’ PERSONALITY; CONSTANT OR INDIVIDUAL DIFFERENCES IN CHANGE? A TRANSACTIONAL ANALYSIS APPROACH - Booth, L.; Parr, J. (European Scientific Journal, ESJ, 2013)
It is considered in diagnostic radiography that incompatible personalities of student radiographers can have a detrimental influence on interpersonal relationships, student retention and job satisfaction. For this reason some authors argue that personality should be a criteria that is measured prior to enrolment onto the radiography programme. However recent evidence argues that personality can change and is influenced by education, clinical and life experience, suggesting that personality assessment would be an inappropriate measure prior to student selection. This research aimed to determine whether there were different personality profiles of student radiographers across the educational tenure (3 years). To facilitate this aim a cross sectional descriptive study was undertaken, using the Transactional Analysis Subscales of the adjective check list as the data collection tool. The data was analysed using both descriptive and inferential statistics (Krusal Wallis). The results demonstrated a significant difference between the personality profiles of diagnostic radiographers across the educational tenure, suggesting that education, clinical and life experience do impact on student radiographer’s personality.